2022
DOI: 10.36941/ajis-2022-0038
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Efficiency Products: A Guideline for Teak Utilization Over 13-15 Years

Abstract: The objective of this research was to develop a guideline for teak utilization over 13-15 years. In this case, the population comprised one thousand, one hundred, and twenty-nine participants at the academic conference and Thai natural resource exhibition, while the group sampling included a visitor group comprising ninety-four people at the exhibition and young teak product sales at the level of deviation of 10 percent. In this case, a 5-point rating scale was used as a research tool employing structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…From the tangible knowledge, this would show the results as new products that could generate income for the elderly. Thus ,it would be considered as a development that would create sustainability in the lifestyle of the elderly people (Egwutvongsa, 2023;Kijmongkolvanich et al, 2023;Lertchamchongkul & Egwutvongsa, 2022;Magistretti et al, 2021). From the three factors that consisted of six variables, this would use the fusion of creative thinking similar to design thinking that would integrate diverse knowledge b efore applying the arising creativity to solve the desired problem .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the tangible knowledge, this would show the results as new products that could generate income for the elderly. Thus ,it would be considered as a development that would create sustainability in the lifestyle of the elderly people (Egwutvongsa, 2023;Kijmongkolvanich et al, 2023;Lertchamchongkul & Egwutvongsa, 2022;Magistretti et al, 2021). From the three factors that consisted of six variables, this would use the fusion of creative thinking similar to design thinking that would integrate diverse knowledge b efore applying the arising creativity to solve the desired problem .…”
Section: Discussionmentioning
confidence: 99%
“…Local Materials: Local materials could be made into products that would meet the needs of locals, which would appear to be popular for use in the area. Moreover, this would be considered to add economic value to local materials, and the materials would be highly suitable for the local area by helping solve local economic and environmental problems (Djati et al, 2015;Egwutvongsa, 2023;Lertchamchongkul & Egwutvongsa, 2022). Creative Ideas: Thinking skills would need to be suitable for the 21 st century, and creativity would come from flexible thinking combined with critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was found that the nitrogen value was the highest, the second was potassium, and the last was phosphorus. In addition, these were considered to be important nutrients that helped plants grow well in accordance with the building pattern with organic farming or natural farming (Lertchamchongkul et al, 2022). As a result, the practice of organic farming is a method of farming based on the balance of nature to create biodiversity by reducing dependence on foreign substances, synthetic chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…It also contributes to house cleanliness which will benefit cattle health in such a way that it does not contribute to the accumulation of disease vectors. It has the nature of the relationship between the environment and the surrounding society that facilitates the emergence of shared environmental responsibility (Lertchamchongkul, T., et al, 2022;Piromgarn, T., et al, 2023) and The new cow dung processing machine will reduce the steps in bringing cow dung to work or storage This will help achieve positive results as follows. 1) Reduce the time in the sun.…”
Section: Discussionmentioning
confidence: 99%